Village poultry in Ethiopia socio-technical analysis and learning with farmers - Asgedom, A.H. (Wageningen University & Research, 2007)
In developing countries village poultry keeping is regarded an important livelihood opportunity for the poor. To improve poultry systems, it is necessary to keep in mind a large number of local complexities. This study aimed to integrate participatory-, survey- and model-based approaches to socio-technical analysis and mutual farmer-researcher learning about constraints to and opportunities for village poultry development in Ethiopia. The study applied a combined technography and systems approach as an input in analyzing possibilities for poultry development in terms of context-mechanism-outcome. To this end it used as data collection methods individual and open-group interviews, a cross-sectional stratified random survey, farm-recording, a market survey, and village-poultry modelling. Feed-back workshops were organised to share between farmers and researchers the data collected through farm-recording and to learn about outcomes of simulation scenarios for identifying improvement options of village poultry systems. Village poultry significantly contributed to the livelihoods of poor households: economically as starter capital, as a means to recover from disasters, as an accessible protein source and for income and exchange purposes, and socio-culturally for mystical functions, hospitality and exchange of gifts to strengthen social relationships. Poor households used sharing arrangements to have access to poultry. Distance to markets influenced flock sizes and poultry marketing organization. Religious festival days were associated with increased poultry consumption and sales, and fasting periods with decreased consumption. Farm-recording was as a first entry point to learn about how farmers participate in research. It transpired that researchers needed to understand the religious and customary norms of the community and adjust the data collection tools and procedures to fit these norms. As a second entry point, farm recording information was presented back to farmers to validate the data and to discuss with farmers the reasons of variation between households. A third entry point for sharing between researchers and farmers was modelling and simulation. Information from literature was used for development of a village-poultry model. The study documented experiences of how the modelling process was used to engage farmers and researchers in joint learning about village poultry keeping. The present study has indicated that through the combination of multiple approaches and methods researchers can arrive at better understanding of constraints affecting farmers’ reality. This implies more relevant problem definition and therefore a potentially more effective technology development process. The study confirms that village poultry research and development are not only about finding technical solutions but also involve addressing household livelihoods, and institutional and policy issues from a social science perspective.